Low emotion differentiation: An affective correlate of binge eating?. Issue 3 (16th December 2019) - Mikhail, Megan E.; Keel, Pamela K.; Burt, S. Alexandra; Neale, Michael; Boker, Steven; Klump, Kelly L.
Abstract: Background: Low emotion differentiation (the tendency to experience vague affective states rather than discrete emotions) is associated with psychopathology marked by emotion regulation deficits and impulsive/maladaptive behavior. However, research examining associations between emotion differentiation and dysregulated eating is nascent and has yet to incorporate measures of clinically significant binge eating. Different measures of emotion differentiation have also been used, impeding cross‐study comparisons. We therefore examined associations between several emotion differentiation measures and binge eating‐related phenotypes across a spectrum of severity. Methods: Women ( N = 482) from the Michigan State University Twin Registry completed the Positive and Negative Affect Schedule (PANAS) daily for 45 consecutive days. Three measures of negative/positive emotion differentiation (NED/PED) were created using the intraclass correlation coefficient (ICC), average interitem correlation, and average daily variance between negative/positive emotion ratings on the PANAS. Associations between NED/PED measures and emotional eating (EE) and a history of binge eating episodes (BEs) were then examined, controlling for affect intensity and BMI. Results: Lower PED was associated with greater odds of BEs across the ICC and average interitem correlation measures, and more EE on the daily variance measure. Findings involving NED were less consistent; lower NED was associated with greater EE and greater odds of BEs using the daily variance measure only. Conclusion: Low PED is associated with clinically significant binge eating, and some aspects of NED may also be relevant for binge eating‐related phenotypes. Further research examining the constructs captured by different emotion differentiation measures and their relevance to binge eating is needed.